2019
DOI: 10.3390/ma12172658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bias Voltage on Mechanical Properties of HiPIMS/RFMS Cosputtered Zr–Si–N Films

Abstract: Zr–Si–N films with atomic ratios of N/(Zr + Si) of 0.54–0.82 were fabricated through high-power impulse magnetron sputtering (HiPIMS)–radio-frequency magnetron sputtering (RFMS) cosputtering by applying an average HiPIMS power of 300 W on the Zr target, various RF power levels on the Si target, and negative bias voltage levels of 0–150 V connected to the substrate holder. Applying a negative bias voltage on substrates enhanced the ion bombardment effect, which affected the chemical compositions, mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Mahato et al [15] reported changes in crystalline phases and grain size following the adjustment of nitrogen content. Applying a negative bias voltage to the substrate has been shown to increase the kinetic energy of the bombarding positive ions, which increases the adatom mobility (ion-bombardment-enhanced diffusion), re-sputtering, and atomic peening [16]. Biswas et al [17] reported that higher bias voltages tend to improve the density of thin films by enhancing the intensity of ion bombardment, however, excessively high bias voltages can compromise the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Mahato et al [15] reported changes in crystalline phases and grain size following the adjustment of nitrogen content. Applying a negative bias voltage to the substrate has been shown to increase the kinetic energy of the bombarding positive ions, which increases the adatom mobility (ion-bombardment-enhanced diffusion), re-sputtering, and atomic peening [16]. Biswas et al [17] reported that higher bias voltages tend to improve the density of thin films by enhancing the intensity of ion bombardment, however, excessively high bias voltages can compromise the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high power impulse magnetron sputtering (HIPIMS), as an alternative to di-rect current magnetron sputtering (DCMS), has attracted extensive attention from many re-searchers and the industry (Purandare et al, 2020;Chen et al, 2019). It utilizes high peak target power and extremely low duty cycle to generate high-density plasma and highly ionized sputtered particles to improve the microstructure and mechanical properties of coatings (Badini et al, 2019;Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bias sputtering increased the kinetic energy of charged ions, which enhanced the mobility of sputtered species and resulted in re-sputtering and atomic peening [26][27][28]. The re-sputtering of light adatoms could affect the atomic compositions of M-Si-N films [29,30]. Therefore, this study investigated variations in the mechanical properties and wear resistance of sputtered W-N and W-Si-N films by adjusting the nitrogen flow ratio and substrate bias.…”
Section: Introductionmentioning
confidence: 99%